Cocopeat Growing Medium Composition and Phosphorus Fertilizer Dose on the Growth and Yield of Taro (Colocasia esculenta L.) - Sartono Joko Santosa; Kharis Triyono; Elly Istiana Maulida (Acitya Wisesa: Journal of Multidisciplinary Research, 2026)
Taro (Colocasia esculenta L.) is a nutritionally significant tuber crop with considerable export potential, yet its productivity in Indonesia remains constrained by suboptimal cultivation practices, particularly with respect to growing medium composition and fertilizer management. This study investigated the effects of cocopeat-enriched growing medium compositions and phosphorus fertilizer doses, as well as their interaction, on the vegetative growth and yield characteristics of taro. A factorial experiment arranged in a Completely Randomized Design (CRD) was conducted from March to December 2025 at the TPH Tohudan Seed Garden, Karanganyar Regency, Central Java, Indonesia, at an altitude of 140 metres above sea level on regosol soil. Three growing medium compositions were evaluated, comprising soil and manure without cocopeat (M0), soil, cocopeat, and manure at 3:1:1 (M1), and soil, cocopeat, and manure at 3:2:1 (M2), combined with four phosphorus fertilizer doses of 0, 100, 200, and 300 kg/ha, equivalent to 0, 7.5, 15.0, and 22.5 g per plant, respectively. Each treatment combination was replicated three times, yielding 36 experimental units. Results indicated that growing medium composition exerted a highly significant effect on all vegetative parameters, including plant height, number of leaves, leaf length, stem length, and stem diameter, with the 3:1:1 ratio producing the highest mean leaf length of 32.46 cm. Phosphorus fertilizer significantly affected tuber sugar content, with the dose of 7.5 g per plant yielding the highest mean sugar content of 2.78%. No significant interaction between the two factors was detected for any parameter measured.